Exercise to Promote Pupil Securitability - Buliņš, Jānis; Jansone, Rasma; Bautre, Inese; Bula-Biteniece, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Health and safety is based on the choices that people make during lifetime. Each of us chooses to act safely or unsafely, healthy or unhealthy. Specific risk group is children and youngsters. Children and young people often have a desire to test their independence, build a personal identity and expand the social life, so young people often experiment also with different types of behavior. In the situations not favorable to health and safety children and young people behavior often do not comply with their knowledge of how to act. Human (human securitability is an internationally-known concept that characterizes human adaptability skills in a rapidly changing environment. Are distinguished 7 human securitability aspects: health, economic, personal (physical), ecological securitability, nutritional, community and political securitability. In the National development plan (NDP) 2020 strategy one of the priorities is human securitability provision. In our study, we analyzed the personal (physical) securitability of educational institutions. A person with a low sense of securitability feels threatened, does not want to use the opportunities of personal growth, trust others and cooperate with them at workplace and in collectives, does not want to participate in the state national development process, and therefore does not contribute to national growth. The pupils are able to learn successfully at school, develop their ability to form a personality only in an environment with a sustainable securitability. The pupil parents can successfully work and act only in the case they are absolutely certain about their children securitability at school, where they spend most of the working day: at schools, in after-school hobby groups, in sports trainings. Creating a safe environment at schools and being educated, growing and developing in this environment, the pupils form understanding of the necessity for a safe and healthy environment and its importance, and develop motivation to keep it for the needs of family, society and the public. In strengthening securitability equally important is knowledge and skills to act in different situations. Researching education policy documents, the authors draw the conclusion that it is necessary on a state level to strengthen the securitability of each Latvian resident and the issues related to state securitability in educational institutions and society as a whole. Sports teacher can contribute to the promotion of pupil securitability, using the subject content as the means. Human securitability can be promoted by knowledge acquisition and skills development in securitability-oriented sports lesson.